2014
DOI: 10.1021/ol502073t
|View full text |Cite
|
Sign up to set email alerts
|

Photoinduced Skeletal Rearrangement of Diarylethenes Comprising Oxazole and Phenyl Rings

Abstract: A novel photochemical rearrangement of diarylethenes bearing oxazole and benzene derivatives as aryl moieties that results in the formation of polyaromatic systems was investigated. The mechanism of the transformation includes photocyclization, sequential [1,9] and [1,3]-hydrogen shifts, as well as a lateral oxazole ring-opening process. It was shown that this reaction can be an effective synthetically preparative method for the preparation of naphthalene (polyaromatic) derivatives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
47
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 49 publications
4
47
0
Order By: Relevance
“…Krayushkin et al recently reported dark bleaching processes that occurred in DAE-related substances possessing one hydrogen atom and am ethyl group. [17] The 1D NOE and 2D experiments (COSY,H MQC, and HMBC) were carried out to determine the structure of the thermally generated byproduct (see Figures S5 and S6 in the Supporting Information). The HMQC experiment provedt ob eu seful, since it showedt hat the singlet signal at d = 3.81 ppm of one proton did not correlate with ac arbona tom.…”
Section: Spectroscopic Properties Of Derivatives 3a Ndmentioning
confidence: 99%
“…Krayushkin et al recently reported dark bleaching processes that occurred in DAE-related substances possessing one hydrogen atom and am ethyl group. [17] The 1D NOE and 2D experiments (COSY,H MQC, and HMBC) were carried out to determine the structure of the thermally generated byproduct (see Figures S5 and S6 in the Supporting Information). The HMQC experiment provedt ob eu seful, since it showedt hat the singlet signal at d = 3.81 ppm of one proton did not correlate with ac arbona tom.…”
Section: Spectroscopic Properties Of Derivatives 3a Ndmentioning
confidence: 99%
“…Diarylethene 4a based on oxazole and benzene rings underwent a photorearrangement to a naphthalene derivative. 42 Compound 4b (bearing benzene and imidazo[1,2-b]pyridine as the substituents), as well as parent ketone 3b, showed unexpected stability under the action of light. On the contrary, compounds 4c,e-i comprising two heterocycles as aryl moieties (excluding anthracene derivative 4d, which has no photochromic properties because of strong fluorescence) exhibited typical photochromic properties (Scheme 5).…”
Section: Methodsmentioning
confidence: 99%
“…On the basis of the experimental results and literature, 19,20,24,25 a two-step mechanism for the cyclization of 3-iodoavones 1 with p-excessive ve-membered heteroarenes 2 has been proposed. Initially, the photo-induced hemolytic cleavage of the C-I bond of 1 under UV light irradiation gave the radical intermediate A.…”
Section: Electrophilic Aromatic Substitution (Eas)mentioning
confidence: 99%
“…[21][22][23][24] Finally, the cyclization product 3 was formed via the syn-elimination of a hydrogen molecule from intermediate G along with the restoration of the aromaticity of the conjugated system.…”
Section: 20mentioning
confidence: 99%